Pengembangan Potensi Wisata Mangrove Melalui Kegiatan Penyuluhan, Pembibitan dan Penanaman Mangrove di Kawasan Pesisir Suppa - Bibin, Muhammad; Ardian, Ani (Jurnal Pemberdayaan Pariwisata; Vol 2 No 1 (2020): Jurnal Pemberdayaan Pariwisata, 2020)
Mangrove forest located on the coast of Tasiwalie Village, Suppa Subdistrict, is decreasing in area because it has been converted into ponds and seaweed farming. The damage to the mangrove forest has an impact on the community of Tasiwalie Village, which is the decrease in the number of fishermen's catches, the reduction in the source of clean water and the community's house being flooded every time the tide is rising. Therefore mangrove tree planting activities need to be done to overcome the problem of damage to the mangrove forest. The purpose of this activity is for the community to take an active role in efforts to conserve mangrove forests and foster community knowledge about the importance of protecting and preserving mangrove forests. The method used in this activity is counseling regarding the use of mangrove potential and mangrove planting practices. The counseling phase was in the form of material delivery and discussion about the potential of mangrove forests and mangrove planting techniques carried out which were carried out at the Tasiwalie Village Hall. The practice of mangrove planting is carried out in the coastal area of ​​Tasiwalie Village, Suppa District. With the extension program and the practice of planting mangroves directly, it is hoped that it can foster knowledge and active role of the community in efforts to conserve mangrove forests.